A SIMULATION-BASED APPROACH FOR IDENTIFYING AND ANALYZING THE WATER DISTRIBUTION NETWORK OF LHOKSEUMAWE CLEAN WATER SUPPLY - Helmy, Iqbal Adinata Setia; Nanda Savira Ersa; Helmy, Wesli; Usrina, Nura; Hafli, T. Mudi (Lingkar: Journal of Environmental Engineering, 2025)
Lhokseumawe City faces significant clean water distribution challenges due to increasing demand from population and economic growth. This study aimed to identify and evaluate the performance of the existing water distribution network using WaterCAD V8i. The methodology involved projecting water demand until 2033 based on 10 years of population data and conducting a hydraulic simulation of the current pipeline system. The simulation results showed that the 2023 clean water demand was 84.5 liters per second, with projections showing a significant increase by 2033. The analysis identified critical operational issues, including backflow in pipe segments P-230 and P-235 and extreme pressure loss gradients in others, with segment P-276 reaching 275 psi during peak hours. It was concluded that the network requires optimization to meet future demand efficiently. Improvement recommendations include replacing critical pipes, resetting valves, and adding pressure regulators to optimize flow.